DESAIN SISTEM INFORMASI KELENGKAPAN FORMULIR INFORMED CONSENT RAWAT INAP DENGAN METODE AGILE - Ririn Nur Fajrin; Yuyun Yunengsih; Rini Suwartika Kusumadiarti (POLITEKNIK PIKSI GANESHA, 2025)
Completeness of informed consent forms is a prerequisite for clinical quality and legal protection in inpatient services. However, in many hospitals, informed consent analysis is still combined with general summaries of medical record incompleteness, so analysis of each informed consent component is not carried out specifically. This leads to a lack of focused monitoring, potentially reducing the quality of medical records. This study designed and evaluated an information system to analyze the completeness of informed consent in an integrated, accurate, and actionable manner. The system development method followed the Agile (Scrum) framework. Agile is an iterative and flexible software development approach that emphasizes team collaboration and rapid response to change. The main stages of the Agile method include: (1) Plan; (2) Design; (3) Develop; (4) Test; (5) Deploy; (6) Review. It is concluded that the digitalization of informed consent completeness analysis based on Agile provides a flexible and adaptive solution for improving medical record quality and patient safety. Further work is recommended in the form of integration with electronic medical records, the addition of quality indicator dashboards, and controlled trials to assess the impact on process efficiency and compliance.